Geomorphic conditions and anthropogenic irrigation as drivers of CO2 and CH4 emissions in Heihe River - Zhiheng Du; Wenhan Hu; Hao Cui; Lei Wang; Jingfeng Liu; Fangping Yan; Rinat Manasypov; Changlian Tao; Renjun Wang; Jing Luo; Chuntan Han; Xiqiang Wang (Global and Planetary Change, 2026)

Metal-free activation of peroxymonosulfate by natural organic acid or inorganic acid for wastewater disinfection and emerging contaminants degradation - Ying Liu; Jingfeng Gao; Yameng Wang; Yan Guo; Yi Zhang (Chemical Engineering Journal, 2026)

Masked ecological risk: Stable anammox performance conceals resistance genes propagation under short-term non-antibiotic antimicrobials stress - Qiyue Zuo; Jingfeng Gao; Jinming Zhang; Tianyi Lu; Ke Zhang; Ke Li; Feifei Gao; Yameng Wang; Yan Guo (Bioresource Technology, 2026)

Impacts of sodium benzoate and lysozyme on nitrification performance and resistance genes: Acute effects of single and co-exposure at different concentrations - Feifei Gao; Jingfeng Gao; Yameng Wang; Yan Guo; Ke Li; Qiyue Zuo; Tianyi Lu (Journal of Hazardous Materials, 2026)

Projecting city-scale energy performance under future weather scenarios through urban building energy modelling incorporating cluster archetypes - Jingfeng Zhou; Jiying Chen; Kaixuan Wang; Bingyu Xu; Xuhui Lin; Jiayi Yan; Meng Wang (Sustainable Cities and Society, 2025)

Radical-free ultra-rapid disinfection: Application of the periodate/Mn(II) system in eliminating antibiotic-resistant bacteria and genes and degrading emerging contaminants - Yameng Wang; Jingfeng Gao; Yan Guo; Lei Wei; Ying Liu; Feifei Gao; Qiyue Zuo; Ke Li (Journal of Hazardous Materials, 2025)

Preparation and characterization of glutamine/chito-oligosaccharide modified zein nanoparticles: Controlled release naringin and anti-diabetes - Yiyan Guo; Mingze Xu; Jiapeng Chen; Jingfeng Che; Wenqing Zhu; Yuxin Zheng; Wanting Huang; Wenjun Dai; Hong Chen; Limin Zhai; Li Zhang; Yan-Qing Guan (Food Chemistry, 2025)

Mechanical Behavior and Fracture Evolution of Non-Persistent Rock Joints Using Digital Image Correlation - Xinggang Wang; Xin Jin; Shuaishuai Wang; Jingfeng Shi; Yong Xu; Shuqi Ma; Qilin Yan (Geotechnical and Geological Engineering, 2025)

The Sustained-Release Oxygen Granule Preparation and Its Application in the Transportation of Live Sea Cucumber Apostichopus Japonicus - Yimeng Li; Jinghe Sun; Yan Zhou; Liming Sun; Jingfeng Yang (Journal of Aquatic Food Product Technology, 2025)

Decadal transport of trace elements in a cave system based on 16 years monitoring data: Implications for paleoclimate reconstruction - Xin Fu; Yan Yang; Jingyao Zhao; Yidong Li; Xiaomin Chen; Zhimao Ye; Mingyang Li; Jingfeng Lin; Yanzhi Xu (Applied Geochemistry, 2025)

Identification of carbon dioxide and methane emission characteristic across Heihe River, China - Wenhan Hu; Zhiheng Du; Lei Wang; Fangping Yan; Chuntan Han; Xiqiang Wang; Changlian Tao; Jingfeng Liu (Science of The Total Environment, 2025)

The influence mechanism of environmental factors on DGT adsorbing sulfonamides and the migration between water and sediment - Peng Zhang; Jingfeng Yan; Hao Ji; Linke Ge; Yanying Li (Journal of Environmental Sciences, 2025)

Construction, characterization, and properties of a probiotic delivery system based on oxidized high amylose starch - Bin Zhang; Chenxin Wang; Shuang Liang; Shuang Song; Yinghuan Fu; Chunqing Ai; Jingfeng Yang; Chengrong Wen; Chunhong Yan (Food Research International, 2025)

Gastroprotective effect of fucoidan from Sargassum siliquastrum against ethanol-induced gastric mucosal injury - Jinghe Sun; Tingting Yan; Yuying Zhang; Chengrong Wen; Jingfeng Yang (Food Research International, 2025)

In situ construction of ion/electron conductive components via lithiation strategy enhancing cycling capability and initial Coulombic efficiency of Si anode - Jingfeng Cao; Xiang Yan; Dan Li; Liuyi Hu; Tiansheng Chen; Weiwei Gao; Wenlong Song; Xinhui Xia; Yang Xia; Wenkui Zhang; Hui Huang (Chemical Engineering Journal, 2025)

An overview on the legacy and risks of Polychlorinated Biphenyls (PCBs) and Organochlorinated Pesticides (OCPs) in the polar regions - Peng Zhang; Jing Wang; Andrew Sweetman; Linke Ge; Rongguang Xing; Hao Ji; Jingfeng Yan; Qian Xiao; Yaqing Cui; Hongrui Ma; Sisi Xu (Marine Pollution Bulletin, 2024)

HMS optical fiber gas sensor based on double-layer WO3@CQDs porous film modified cladding for detecting 2-butanone gas at room temperature - Yan-nan Wang; Jingfeng Li; Zhiqiang Yang; Zhenyu Yuan; Jin Li; Fanli Meng (Chemical Engineering Journal, 2024)

PGE2 Overexpressing Human Embryonic Stem Cell Derived Mesenchymal Stromal Cell Relieves Liver Fibrosis in an Immuno-suppressive Manner - Yan Zhong; Xiaohao Hu; Jingfeng Liu (Stem Cell Reviews and Reports, 2024)

Teacher-student guided knowledge distillation for unsupervised convolutional neural network-based speckle tracking in ultrasound strain elastography - Tianqiang Xiang; Yan Li; Hui Deng; Chao Tian; Bo Peng; Jingfeng Jiang (Medical & Biological Engineering & Computing, 2024)

Soil moisture retrieval by a novel hybrid model based on CYGNSS and Sun-induced fluorescence data - Yan Li; Songhua Yan; Jianya Gong; Jingfeng Xiao; Milad Asgarimehr; Jens Wickert (Journal of Hydrology, 2024)

Oxygenated storage alleviates autolysis of the sea cucumber Apostichopus japonicus during transport - Yan Zhou; Jie Zheng; Jun Zhao; Shuang Li; Jie Xing; Chunqing Ai; Chenxu Yu; Sheng Yang; Jingfeng Yang (Aquaculture International, 2023)

A comprehensive review of calcium and ferrous ions chelating peptides: Preparation, structure and transport pathways - Qiaoji Tian; Yan Fan; Li Hao; Jie Wang; Chensi Xia; Jingfeng Wang; Hu Hou (Critical Reviews in Food Science and Nutrition, 2023)

Revisiting the role of transpiration in the variation of ecosystem water use efficiency in China - Huaiwei Sun; Mengge Lu; Yong Yang; Jianing Chen; Jingfeng Wang; Dong Yan; Jie Xue; Wenxin Zhang (Agricultural and Forest Meteorology, 2023)

The Intestinal Microbiota Involves in the Deterioration of Live Sea Cucumber During Storage - Tingting Yan; Chunqing Ai; Haoyang Ou; Shuang Song; Sheng Yang; Jingfeng Yang (Journal of Aquatic Food Product Technology, 2023)

Study on the effects of the different polar group of EPA-enriched phospholipids on the proliferation and apoptosis in 95D cells - Yao Guo; Qin Zhao; Yingying Tian; Yuanyuan Liu; Ziyi Yan; Changhu Xue; Jingfeng Wang (Marine Life Science & Technology, 2021)
EPA-enriched phosphatidylcholine (EPA-PC) and EPA-enriched phosphatidylethanolamine (EPA-PE) are newly identified marine phospholipids. The polar group of phospholipids is known to influence EPA-phospholipid activity. However, the differences in anti-tumor effects between EPA-PC and EPA-PE have not been reported. In this study, we evaluated the effects of two forms of EPA on the proliferation and apoptosis in the lung-cancer cell line 95D as well as possible molecular mechanisms. Our results showed that EPA-PC effectively inhibited proliferative activity and promoted apoptosis of 95D cells in a dose-dependent manner, while EPA-PE had no effect on cell proliferation, although it slightly promoted apoptosis. Western blot results showed that EPA-PC and EPA-PE upregulated the expression of PPARγ, RXRα, and PTEN, and downregulated the PI3K/AKT signaling pathway. Furthermore, EPA-PC and EPA-PE induced the expression of the pro-apoptotic gene, Bax, and reduced the expression of the anti-apoptotic gene, Bcl-xl. Additionally, EPA-PC and EPA-PE promoted the release of cytochrome c and activated the apoptotic enzyme-cleaved caspase-3. These data suggest that the anti-tumor effect of EPA-phospholipids may be exerted via a PPARγ-related mechanism. EPA-PC was more efficacious as compared to EPA-PE, which might be due to the different polar groups of phospholipids.

Condition dependence of advertisement calls in male African clawed frogs - Xiaocui Wang; Zhi-Jun Zhao; Yan Cao; Jianguo Cui; Yezhong Tang; Jingfeng Chen (Journal of Ethology, 2019)

Removal of hexavalent chromium from water by modified sponge iron particles and insights into mechanism - Guilin Zhu; Junde Song; Weihong Dong; Jingfeng Lu; Yan Wang; Weinan Jiang; Ping Guo (Environmental Science and Pollution Research, 2018)

Preparation, Gel Electrophoresis Analysis, and Nutritional Evaluation of a Functional Krill Protein Concentrate with Low Fluoride Level from Antarctic krill ( Euphausia superba ) - Li’ang Yin; Xiaoming Jiang; Yan Fan; Jingfeng Wang; Changhu Xue; Yong Xue (Journal of Aquatic Food Product Technology, 2017)

Processes of coastal ecosystem carbon sequestration and approaches for increasing carbon sink - Yao Zhang; MeiXun Zhao; Qiu Cui; Wei Fan; JiaGuo Qi; Ying Chen; YongYu Zhang; KunShan Gao; JingFeng Fan; GuangYi Wang; ChongLing Yan; HaoLiang Lu; et al. (Science China Earth Sciences, 2017)

Spatial Abundance, Diversity, and Activity of Ammonia-Oxidizing Bacteria in Coastal Sediments of the Liaohe Estuary - Yongkai Chang; Jingfeng Fan; Jie Su; Hongxia Ming; Wen Zhao; Yan Shi; Fengyun Ji; Limei Guo; Shuaijun Zan; Bochao Li; Hao Guo; Daoming Guan (Current Microbiology, 2017)

Effects of Epstein-Barr virus infection on the development of multiple myeloma after liver transplantation - YeWei Zhang; HeWei Zhao; Xia He; SuWen Zheng; TaiHong Wang; DongLiang Yan; JingFeng Sun; Xiang Lu; JianFei Wen; Wan Yee Lau (Science China Life Sciences, 2012)